Corporate Culture and Organizational Performance: A Case Study of National Water and Sewerage Corporation (Nwsc) Ibanda Area - Peace, Tumushabe (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate Training in Partial Fulfilment of the Requirements for the Award of a Master’s Degree in Business Administration of Kabale University